THE ROLE OF ENTREPRENEURSHIP EDUCATION IN IMPROVING STUDENTS' CREATIVITY IN ENTREPRENEURSHIP - Yayuk Yuliana; Leni Handayani; Dedi Iskandar Batubara; Camelya Adelyani Br Hutagalung (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study is to examine the role of entrepreneurship education in improving students' creativity in entrepreneurship. The results of this study are expected to be input for the development of entrepreneurship education in universities in order to encourage the birth of intellectuals who choose careers as entrepreneurs. Ultimately, with the increasing number of student graduates who choose to become entrepreneurs, the problem of limited job opportunities can be overcome, so that it is hoped that economic development in Indonesia will continue to increase and progress. The method used in this study is to use a literature review. Entrepreneurship education is a process or activity carried out in order to instill an entrepreneurial mentality, transmit knowledge and entrepreneurial skills to students through formal educational institutions (universities) and non-formal institutions (training institutions) in an effort to utilize business opportunities. Creativity Entrepreneurship is a driving force that makes someone do a new business as a long-term career. The drive can come from within oneself such as the intention and desire, or from outside such as advice, suggestions and input. Entrepreneurship education plays a very important role in increasing Student Creativity in entrepreneurship.